The Antiquities of Jordan in the Reports of Foreign Explorers and Travelers (The Stage Before the Establishment of the Emirate of Jordan in 1921 AD) - Kafafi, Zeidan (Jordan Journal for History and Archaeology, 2022)
This article studies the foreign explorers and travelers who documented the archaeological heritage of Jordan during the 18th and 19th centuries in their travel reports. The article begins with a summary of the historical and social conditions of Jordan at the time, when Jordan was part of the Ottoman state. The article examines the foreign explorers in three sub-periods: From the end of the Crusader period in the aftermath of the Battle of Hittin in 1187 up to Napoleon’s military expedition to Egypt in 1798. From Napoleon’s military expedition in 1798 up to the establishment of the Western learned societies interested in the antiquities of Palestine, starting with the British Palestine Exploration Fund in 1865. From the establishment of the Palestine Exploration Fund in 1865 up to the establishment of the Emirate of Jordan in 1921. The reports of the travelers and explorers concentrated on sites and regions mentioned in the biblical narratives